Định kiến xã hội - một vỉa hiện thực mới trong tiểu thuyết và truyện ngắn của Nam Cao trước Cách mạng - Nguyễn, Văn Tùng (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TÂN TRÀO, 2021)
The research article focuses on the question of social prejudice in the novels and short stories of Nam Cao before the Revolution. This survey clarifies the position of writer Nam Cao in the trend of literary realism in particular and contributes about the artistic ideas of Nam Cao to modern Vietnamese literature. The author uses the method of documentary research, methods of systematization, generalizations besides some research skills such as analysis, demonstration, comparison... Since then, the research article has clarified the manifestation of the problem of social prejudice through the world of iconography, the environment, the cause of social prejudice, the way of explaining social prejudice and some solutions of the writer.